2018
DOI: 10.1148/radiol.2018172104
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Number of Measurements in Liver Point Shear-Wave Elastography: Factors that Influence the Number and Reliability of Measurements in Assessment of Liver Fibrosis in Clinical Practice

Abstract: Purpose To identify the minimum number of measurements required for the noninvasive assessment of liver fibrosis by using point shear-wave elastography (pSWE) and determine whether the use of a reliability indicator such as interquartile range [IQR]-to-median ratio will affect diagnostic performance. Materials and Methods Ten liver shear-wave velocity (SWV) measurements by pSWE were obtained in 232 participants. Interclass correlation coefficients (ICC) between the median of the first two through the first nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…This analysis was performed for each of the 25 radiomics features being investigated. Selection of radiomics features least impacted by contouring variability was based on the lower confidence interval of ICC (ICC LB ) for all 10 raters and a threshold of ≥0.950 (i.e., an error of less than 5% for worst case scenario) was used as the cutoff value 33 . The impact of decreasing the number of raters for the top performing features was explored by employing a leave-p-out analysis 34 .…”
Section: Resultsmentioning
confidence: 99%
“…This analysis was performed for each of the 25 radiomics features being investigated. Selection of radiomics features least impacted by contouring variability was based on the lower confidence interval of ICC (ICC LB ) for all 10 raters and a threshold of ≥0.950 (i.e., an error of less than 5% for worst case scenario) was used as the cutoff value 33 . The impact of decreasing the number of raters for the top performing features was explored by employing a leave-p-out analysis 34 .…”
Section: Resultsmentioning
confidence: 99%
“…In the available literature, the number of acquisitions taken in children varies from 1 to 24 [11]. Less than 10 measurements may be required in future studies as excellent reproducibility and accuracy have been reported with a lower number of acquisitions [30]. It has been reported that the number of acquisitions may have little influence on the diagnostic accuracy compared to the variability of the measurements [30].…”
Section: General Technical Advicementioning
confidence: 99%
“…Less than 10 measurements may be required in future studies as excellent reproducibility and accuracy have been reported with a lower number of acquisitions [30]. It has been reported that the number of acquisitions may have little influence on the diagnostic accuracy compared to the variability of the measurements [30]. Therefore, in pediatric studies, the number of measurements taken may be based on the child's age and the cooperation during the examination.…”
Section: General Technical Advicementioning
confidence: 99%
“…On practical grounds pSWE techniques tend to require a higher number of valid measurements to achieve an accurate median stiffness value (recommendation is 6 measurements or even more if reliability criteria are not fully met). 9,10 This is expected to be related to the fact that they sample a smaller portion of tissue and are therefore more prone to suffer the heterogenous involvement of the liver in case of significant fibrosis (since the sampled portion may fall in a regenerative nodule as well as in a large scar). On the other hand, bidimensional SWE, is often accurate after only 35 measurements, but may be more prone to subjective judgement in all those technologies in which the location of the Region of Interest (ROI) within the stiffness box is freely chosen by the operator.…”
Section: Confounding Factors In the Assessment Of Liver Fibrosis By Ementioning
confidence: 99%